5PSQ-070 Influence of pathology in injection pain reduction with a new formulation of original adalimumab. (March 2019) - Martínez-Casanova, J; Acin, P; Carballo, N; Gonzalez, R; Navarrete Rouco, E; Perez García, C; Gonzalez-Colominas, E; Tarason, L; Grau, S; Ferrández, O
Abstract : Background: Drug injection-related pain is associated with a poor treatment adherence. To reduce it, a new subcutaneous formulation of adalimumab free of citrate and with a smaller volume injection and calibre needle has been brought to the market. Purpose: The objective was to assess the influence of the treated pathology and associated factors on the pain reduction due to the switch to the new formulation of original adalimumab. Material and methods: Prospective study performed during adalimumab's formulation shift (2017) in the outpatient pharmaceutical care area of a tertiary hospital. All patients that had received both formulations were included and classified by the treated pahology. Pain was assessed by the patients through a visual analogue scale (VAS)(0–10 cm). Data collected: demographic, country of origin, injection site, administration frequency, number of doses before the switch, biologic-naïve, VAS score pre- (VASPRE) and post- (VASPOST) formulation switch, concomitant medication. Statistics: median and interquartile range for quantitative (except age, mean (SD)), and% for qualitative variables. Association of several variables with pain reduction was checked through median regression models. Results: Injection pain reduction (VASPOST–VASPRE) was statistically significant for all pathologies (p<0.001). Statistically significant differences observed for: VASPRE: RA vs psoriasis (p=0.0403): IBD vs psoriasis (p=0.0207). Injection pain reduction (VASPOST–VASPRE): IBD vs psoriasis (p=0.0117). For IBD, antidepressants treatment (four patients, 10.81% of IBD cases) was the variable associated with the pain injection reduction (MD=−4.0; 95% CI: −7.26 to −0.74); p=0.018). No variables were identified for the other pathologies. Conclusion: Most patients reported better tolerance to the new formulation of original adalimumab, independently of the pathology. Pain with the ancient formulation was higher in IBD and RA than in psoriasis patients, and pain reduction was higher in IBD than in psoriasis ones. In IBD patients, those receiving antidepressant had a lower perception of pain maybe due to the analgesic action of these drugs. It would be interesting to consider these pain reduction results when developing biosimilar adalimumab formulations. References and/or acknowledgements: None. No conflict of interest.